Control of Fossil Fuel Gas Operating Conditions on the Performance of Carbon Dioxide Capture Process. Issue 1 (April 2021) - Letsholo, I.; Moropeng, M.L.; Mavhungu, A.; Agboola, O.; Fayomi, O.S.I; Moropeng, R.C.
Abstract: The emission of Carbon dioxide (CO2 ) from combustible flue gases is now seen as the key instrumental factor to global warming. The process of post-combustion capture from industrial flue gases via reactive absorption have the capability of substantially reducing the emissions of the greenhouse effect. This paper presents the modelling and simulation of flue gas conditions for carbon dioxide capture process utilizing post-combustion process. The obtained models were simulated using SCILAB 5.5.2 code based software. The results shows a good relevance of the modeling procedure with the fact that the volumetric flow rate of the flue gas and the Amine temperature governs the dynamics of CO2 absorption at the bottom region of the column. It is also noted in the findings that the increase in the volume of the flue gas gives rise to the concentration of CO2 at low temperatures.